Positive plate and lithium ion secondary battery
By installing a base coat containing titanium dioxide, tin oxide and antimony oxide on both sides of the current collector of the positive electrode sheet of the lithium-ion battery, the expansion and contraction phenomenon during overcharging is used to achieve the overcharge protection of the battery and solve the lithium ion The safety hazards of the battery when overcharging and maintain the normal circulation performance of the battery.
Patent Information
- Application Number
- CN202411372740.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-27
AI Technical Summary
Existing lithium-ion batteries have safety risks when overcharging, which may lead to thermal runaway, fire or even explosion. The existing methods to prevent overcharging affect the normal circulation performance of the battery.
A positive electrode sheet is designed, including a primer layer and a positive electrode active material layer on both sides of the current collector. The primer layer is composed of 50%-70% titanium dioxide, 25%-40% tin oxide and 0%-25% oxidation. Composition of antimony, tin oxide and antimony oxide are coated or mixed on the surface of titanium dioxide to form a coating or mixture, which produces expansion and contraction during overcharging, causing the base coat to detach from the current collector, increase the polarization of the battery, and increase rapidly. High voltage to overcharge cutoff voltage to prevent overcharge failure.
It effectively prevents the battery from overcharging failure, improves the battery's safety, and does not affect the normal cycle performance of the battery, achieving overcharging protection.
Smart Images

Figure CN119208525A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery materials, and in particular to a positive electrode sheet and a lithium-ion secondary battery. Background Art
[0002] With the widespread application of lithium-ion batteries in electric vehicles, energy storage systems and portable electronic devices, their safety issues are receiving increasing attention. Overcharging is one of the common safety hazards in the use of lithium-ion batteries, which may cause thermal runaway, fire or even explosion of the battery. In the prior art, although there are many methods to prevent battery overcharging, such as overcharge protection in the battery management system (BMS) and electrolyte additives, these methods often affect the normal cycle performance of the battery. Summary of the invention
[0003] The present application provides a positive electrode sheet and a lithium-ion secondary battery, which aim to solve the problem that existing lithium-ion secondary batteries cannot take into account both overcharge safety and stable cycle performance to a certain extent.
[0004] In the first aspect, the present application provides a positive electrode sheet, which includes a current collector, a primer layer located on at least one side of the current collector, and a positive electrode active material layer located on the side of the primer layer away from the current collector, the primer layer includes a metal oxide, and the metal oxide includes 50%-70% of titanium dioxide (TiO2), 25%-40% of tin oxide (SnO2) and greater than 0 and less than or equal to 25% of antimony oxide (Sb2O3), based on the total mass of the metal oxide as 100%, the tin oxide and antimony oxide are coated on the surface of titanium dioxide to form a coating layer and / or mixed with titanium dioxide to form a mixture.
[0005] In an optional embodiment, based on 100% of the total mass of the metal oxides, the mass content of titanium dioxide is 55%-65%, the mass content of tin oxide is 26%-36%, and the mass content of antimony oxide is 4%-9%.
[0006] In an optional embodiment, when the tin oxide and antimony oxide are coated on the surface of titanium dioxide to form a coating layer, the thickness of the coating layer is 20-100 nm; the particle size Dv2(50) of the coated titanium dioxide is 0.3-1 μm; and / or,
[0007] When the tin oxide, antimony oxide and titanium dioxide are mixed to form a mixture, the primary particle size Dv(50) of the tin oxide and antimony oxide is 5nm-20nm, the secondary particle size Dv(50) of the tin oxide and antimony oxide is 30nm-80nm; the particle size Dv(50) of titanium dioxide is 250nm-550nm.
[0008] When the tin oxide, antimony oxide and titanium dioxide are mixed to form a mixture, the particle size Dv(50) of the titanium dioxide is the secondary particle size Dv(50) of the titanium dioxide.
[0009] In an optional embodiment, the surface resistance of the primer layer is 5-30 mΩ.
[0010] In an optional embodiment, the XRD spectrum of the primer layer has characteristic peaks at 25.125-25.525°, 26.632-27.032°, 33.996-34.396°, 36.789-37.189°, 37.641-38.041°, 38.401-38.801°, 47.874-48.274°, 52.030-52.430°, 53.752-54.152°, 54.906-55.306°, 62.550-62.950°, 68.642-69.042°, 70.146-70.546° and 74.929-75.329°.
[0011] In an optional embodiment, the positive electrode active material of the positive electrode active material layer includes lithium nickel cobalt manganese oxide, and the chemical formula of the lithium nickel cobalt manganese oxide is as follows: Li(Ni x Co y Mn z )O2, where x+y+z=1, 0.8≤x<1, 0<y<0.2, 0<z<0.2.
[0012] In an optional embodiment, a coating layer is provided on the surface of the lithium nickel cobalt manganese oxide, and the coating layer includes Al, Zr, W and Sr.
[0013] In an optional embodiment, the content A of the Al element, the content B of the Zr element, the content C of the W element and the content D of the Sr element in the positive electrode active material of the positive electrode active material layer satisfy the following relationship:
[0014] 0.16≤A*C / (B*D)≤0.8;
[0015] Among them, 800ppm≤A≤1200ppm, 2500ppm≤B≤3500ppm, 700ppm≤C≤1000ppm, 600ppm≤D≤1000ppm.
[0016] In an optional embodiment, the thickness H2 of the undercoat layer, the thickness H1 of the positive electrode active material layer, the particle size Dv2(50) of the metal oxide of the undercoat layer, and the particle size Dv1(50) of the positive electrode active material of the positive electrode active material layer in the positive electrode sheet satisfy the following relationship:
[0017] 2.67≤{H1*Dv1(50)} / {H2*Dv2(50)}≤833.33;
[0018] Among them, 2μm≤H2≤15μm; 40μm≤H1≤100μm, 1μm≤Dv1(50)≤5μm, 0.3μm≤Dv2(50)≤1μm.
[0019] In an optional embodiment, the thickness H2 of the undercoat layer, the thickness H1 of the positive electrode active material layer, the particle size Dv2(50) of the metal oxide of the undercoat layer, and the particle size Dv1(50) of the positive electrode active material of the positive electrode active material layer in the positive electrode sheet satisfy the following relationship:
[0020] 33.3≤{H1*Dv1(50)} / {H2*Dv2(50)}≤304.76;
[0021] Among them, 50μm≤H1≤80μm, 3μm≤H2≤6μm, 2μm≤Dv1(50)≤4μm, and 0.35μm≤Dv2(50)≤0.8μm.
[0022] Dv2(50) is the particle size corresponding to when the cumulative particle size distribution percentage of the metal oxide in the undercoat layer reaches 50%; Dv1(50) is the particle size corresponding to when the cumulative particle size distribution percentage of the positive electrode active material in the positive electrode active material layer reaches 50%.
[0023] In an optional embodiment, the single-sided coating density of the positive electrode is 7 mg / cm 2 -14mg / cm 2 .
[0024] In an optional embodiment, the compaction density of the positive electrode sheet is 2.9 g / cm 3 -3.5g / cm 3 between.
[0025] In an optional embodiment, the porosity of the positive electrode sheet is 20%-40%.
[0026] In an optional implementation, the surface resistance of the positive electrode sheet is 600-2000 mΩ.
[0027] In an optional embodiment, the primer layer further includes a first binder; preferably, the surface resistance R0mΩ of the primer layer, the surface resistance R1mΩ of the positive electrode sheet, and the content W of the first binder polyvinylidene fluoride in the primer layer satisfy the following relationship:
[0028] 30≤W*R0*R1≤3000;
[0029] Among them, R0 is 5-30, R1 is 600-2000, and W is 1%-5%.
[0030] In an optional embodiment, the primer layer further includes a first binder polyvinylidene fluoride; preferably, the surface resistance R0 of the primer layer, the surface resistance R1 of the positive electrode sheet, and the content W of the first binder polyvinylidene fluoride in the primer layer satisfy the following relationship:
[0031] 192≤W*R0*R1≤1250.
[0032] In an optional embodiment, the first binder comprises polyvinylidene fluoride.
[0033] In a second aspect, the present application provides a lithium-ion secondary battery, comprising the positive electrode sheet described in the second aspect of the present application.
[0034] In an optional embodiment, the charging differential capacitance curve of the lithium ion secondary battery charged at a rate of 2C in a voltage range of 2.5V-6V does not have a characteristic peak between 4.9V-5.5V, or has a characteristic peak P1 between 4V-4.5V and a characteristic peak P2 between 4.9V-5.5V that satisfies the following relationship: <P2 / P1≤0.3。
[0035] In an optional embodiment, when the lithium ion secondary battery is charged and discharged, according to the voltage V and the battery capacity Q, the discharge differential capacitance curve with the voltage V on the horizontal axis and the dQ / dV value obtained by differentiating the battery capacity Q with the voltage V on the vertical axis does not have a characteristic peak between 4.9V and 5.5V, or the peak intensity P1 of the characteristic peak 1 between 4V and 4.5V and the peak intensity P2 of the characteristic peak 2 between 4.9V and 5.5V satisfy the following relationship: <P2 / P1≤0.3。
[0036] The technical solution of this application has the following advantages:
[0037] The present application provides a positive electrode sheet, which includes a current collector, a primer layer located on at least one side of the current collector, and a positive electrode active material layer located on a side of the primer layer away from the current collector, wherein the primer layer includes a metal oxide, and the total mass of the metal oxide is 100%, the metal oxide includes 50%-70% of titanium dioxide, 25%-40% of tin oxide, and greater than 0 and less than or equal to 25% of antimony oxide, the tin oxide and antimony oxide are coated on the surface of the titanium dioxide to form a coating layer and / or are mixed with the titanium dioxide to form a mixture, and by arranging the primer layer on the current collector, the titanium dioxide, tin oxide and antimony oxide in the primer layer expand, shrink, etc. when the battery is overcharged, the primer layer is separated from the current collector, so that the positive electrode sheet lacks electrical connection, the battery polarization increases, and the battery voltage is rapidly increased to the overcharge cut-off voltage, so that the structure of the positive electrode active material is stable, the battery overcharge failure can be effectively prevented, the safety of the battery is improved, thereby achieving overcharge protection, and the normal cycle performance of the battery is not affected.
[0038] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0040] Figure 1 A schematic diagram of the structure of the positive electrode sheet provided in Example A1;
[0041] Figure 2 A schematic diagram of the structure of the positive electrode sheet provided for Comparative Example A1;
[0042] Figure 3 The surface SEM images of the pole pieces prepared in Example A1 and Comparative Example A1;
[0043] Figure 4 The cross-sectional SEM images of the pole pieces prepared in Example A1 and Comparative Example A1;
[0044] Figure 5 : are discharge differential capacitance curves of Example A1 and Comparative Example A1, the solid line is Example A1, and the dotted line is Comparative Example A1;
[0045] Figure 6 XRD curves of the electrode sheet coated with the primer layer in step (3) of Example A1 and the positive electrode sheet prepared in Comparative Example A1;
[0046] Figure 7 This is a SEM image of the pole piece coated with the primer layer in step (3) of Example A1;
[0047] Figure 8 2C-6V overcharge voltage curve and overcharge temperature curve of the secondary batteries prepared in Example A1 and Comparative Example A1;
[0048] Fig. 9 The battery status diagram of the secondary battery prepared in Example A1 and Comparative Example A1 after 2C-6V overcharge, Figure 3 , 4 , 8, and 9, (a) is Example A1, and (b) is Comparative Example A1;
[0049] Fig.10 This is a cross-sectional SEM image of the electrode sheet of the secondary battery prepared in Example A1 after 2C-6V overcharge. DETAILED DESCRIPTION
[0050] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.
[0051] In the description of the present application, it should be noted that the terms "inside", "outside", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present application. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.
[0052] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0053] In addition, the technical features involved in the different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.
[0054] The present application provides a positive electrode sheet and a lithium-ion secondary battery. By arranging an undercoat layer and a positive electrode active material layer on a current collector, the titanium dioxide, tin oxide and antimony oxide in the undercoat layer expand and contract when the battery is overcharged. The undercoat layer separates from the current collector, causing the positive electrode sheet to lose electrical connection, increasing the polarization of the battery, and rapidly increasing the battery voltage to the overcharge cut-off voltage, thereby stabilizing the structure of the positive electrode active material, effectively preventing the battery from overcharging and failing, and improving the safety of the battery, thereby achieving overcharge protection without affecting the normal cycle performance of the battery.
[0055] Specifically, in the first aspect, the present application provides a positive electrode sheet, the positive electrode sheet includes a current collector, a primer layer located on at least one side of the current collector, and a positive electrode active material layer located on the side of the primer layer away from the current collector, the primer layer includes a metal oxide, and the total mass of the metal oxide is 100%, the metal oxide includes 50%-70% titanium dioxide, 25%-40% tin oxide and greater than 0 and less than or equal to 25% antimony oxide, the tin oxide and antimony oxide are coated on the surface of titanium dioxide to form a coating layer and / or mixed with titanium dioxide to form a mixture, TiO2 as the main component of the metal oxide provides good chemical stability and physical properties, SnO2 as a conductive additive, can significantly improve the conductive properties of the primer layer. It helps to form a more dense and uniform conductive network, thereby improving the conductive efficiency of the battery. Sb2O3 as a dopant can further improve the conductive properties and stability of the primer layer. It helps to optimize the structure of the conductive network and improve the conductive uniformity and durability of the coating. By using titanium dioxide, tin oxide and antimony oxide in the above-mentioned specific content, the bottom coating layer has a certain value of impedance. When overcharged, due to the polarization of the positive electrode side, it is easier to reach the overcharge cut-off voltage than the positive electrode without the bottom coating layer. At the same time, the resistance value will not cause the cycle performance of the battery to deteriorate, ensuring that the battery has both high safety performance and long cycle life. As an example, taking the total mass of the metal oxide as 100%, the mass content of titanium dioxide is 50%, 52%, 55%, 60%, 65%, 70% or in the range of any two of the above values, the mass content of tin oxide is 25%, 28%, 30%, 35%, 40% or in the range of any two of the above values, and the mass content of antimony oxide is 4, 5%, 6%, 8%, 9%, 10%, 12%, 15%, 20% or in the range of any two of the above values. The tin oxide and antimony oxide can be coated on the surface of titanium dioxide to form a coating layer, or they can be mixed with titanium dioxide to form a mixture and exist in the bottom coating layer. Compared with the form of a mixture, tin oxide and antimony oxide are coated on the surface of titanium dioxide to form a coating layer, and a close interface contact is formed between them. This interface contact not only enhances the interaction force between different oxides, but also promotes the transmission of electrons at the interface. Compared with a simple mixture, the coating layer structure can more effectively utilize the interface effect and increase the migration rate of electrons, thereby optimizing the conductive properties of the base coating. The coating layer structure enables tin oxide and antimony oxide to be more evenly distributed on the surface of titanium dioxide particles to form a continuous conductive network. This conductive network not only improves the overall conductivity of the base coating, but also makes the current more evenly distributed in the base coating. In contrast, the metal oxide particles in the mixture may be unevenly distributed, resulting in excessive local current density, affecting the performance and safety of the battery.The coating structure can more effectively protect the titanium dioxide core from external environmental influences such as humidity, temperature changes and chemical corrosion. This protection mechanism enables the base coating to maintain a stable structure and performance during long-term use. At the same time, tin oxide and antimony oxide as coating materials also have certain chemical stability, which can further enhance the overall stability of the base coating.
[0056] In an optional embodiment, when the tin oxide and antimony oxide are coated on the surface of titanium dioxide to form a coating layer, the thickness of the coating layer is 20-100 nm; the particle size Dv2(50) of the coated titanium dioxide is 0.3-1 μm. A thicker coating layer will increase the polarization resistance, and the battery safety performance is guaranteed but the cycle performance is not guaranteed. By precisely controlling the thickness of the coating layer and the particle size of the coated titanium dioxide within the above range, the conductive properties of the base coating material can be optimized to achieve a better balance between safety and electrical performance. Among them, the thickness of the coating layer is measured by transmission electron microscopy (TEM). The particle size Dv2(50) of the coated titanium dioxide refers to the particle size D50 of the entire metal oxide coating formed after coating, which is measured by a laser particle size analyzer. For example, the thickness of the coating layer can be 20nm, 40nm, 60nm, 80nm, 100nm or in the range of any two of the above values; Dv2(50) can be 0.3μm, 0.4μm, 0.6μm, 0.8μm, 1μm or in the range of any two of the above values.
[0057] In an optional embodiment, when the tin oxide and antimony oxide are mixed with titanium dioxide to form a mixture, the primary particle size Dv(50) of tin oxide and antimony oxide is 5nm-20nm, and the secondary particle size Dv(50) of tin oxide and antimony oxide is 30nm-80nm; the particle size Dv(50) of titanium dioxide is 250nm-550nm. By precisely controlling the particle size of tin oxide and antimony oxide within the above range, their dispersibility and conductivity in the mixture can be optimized, and the problem of excessive local current density can be solved. Small primary particle size helps to form a denser conductive network, while appropriate secondary particle size can avoid excessive resistance while maintaining dispersibility. As a matrix material, the selection of the particle size of titanium dioxide is crucial to the overall performance of the mixture. Suitable particle size helps to provide sufficient mechanical strength and stability, and is also conducive to forming a larger specific surface area, promoting interaction with tin oxide and antimony oxide. When the particle size is too large, it will increase the resistance to electron transmission, so it is necessary to control it within a reasonable range while ensuring mechanical strength. Wherein, the primary particle size Dv(50) of tin oxide and antimony oxide is the particle size Dv(50) of a single particle in a mixture of tin oxide and antimony oxide, measured by SEM. The secondary particle size Dv(50) refers to the particle size D50 after the primary particle size particles are agglomerated, measured by a laser particle size analyzer. The particle size Dv(50) of titanium dioxide is measured by a laser particle size analyzer. For example, the primary particle size Dv(50) of tin oxide and antimony oxide can be 5nm, 8nm, 10nm, 15nm or within the range of any two of the above values. The secondary particle size Dv(50) of tin oxide and antimony oxide can be 30nm, 40nm, 50nm, 60nm, 80nm or within the range of any two of the above values. The particle size Dv(50) of titanium dioxide can be 250nm, 300nn, 400nm, 4500nm, 550nm or within the range of any two of the above values.
[0058] In an optional embodiment, the XRD spectrum of the primer layer has characteristic peaks at 25.125-25.525°, 26.632-27.032°, 33.996-34.396°, 36.789-37.189°, 37.641-38.041°, 38.401-38.801°, 47.874-48.274°, 52.030-52.430°, 53.752-54.152°, 54.906-55.306°, 62.550-62.950°, 68.642-69.042°, 70.146-70.546° and 74.929-75.329°.
[0059] In an optional embodiment, the surface resistance of the bottom coating is 5-30mΩ. The surface resistance of the bottom coating can be 5mΩ, 10mΩ, 20mΩ, 30mΩ or in the range of any two of the above values. The surface resistance of the bottom coating within this range does not have an adverse effect on the electrical performance of the battery. As the overcharge voltage increases, the polarization phenomenon inside the battery gradually intensifies, and the battery voltage quickly reaches the overcharge cut-off voltage of 6V, thereby effectively preventing the battery from thermal runaway.
[0060] In an optional embodiment, the positive electrode active material of the positive electrode active material layer includes lithium nickel cobalt manganese oxide, and the chemical formula of the lithium nickel cobalt manganese oxide is as follows: Li(Ni x Co y Mn z )O2, wherein, x+y+z=1, 0.8≤x<1, 0<y<0.2, 0<z<0.2. As an example, x can be 0.8, 0.9, 0.99 or within the range formed by any two of the above values. y can be 0.02, 0.05, 0.1, 0.18 or within the range formed by any two of the above values. z can be 0.02, 0.05, 0.1, 0.18 or within the range formed by any two of the above values. The positive electrode active material adopts nickel cobalt lithium manganese oxide, which can greatly reduce the internal resistance of the positive electrode sheet compared with other positive electrode active materials (such as nickel-doped lithium manganese oxide), while improving the structural stability of the positive electrode sheet, thereby improving overcharge safety on the basis of maintaining higher energy density and cycle performance, so that the lithium-ion secondary battery takes into account both overcharge safety and stable cycle performance.
[0061] In an optional embodiment, the surface of the lithium nickel cobalt manganese oxide is provided with a coating layer, and the coating layer includes Al, Zr, W and Sr. Al has excellent thermal stability, can prevent NCM (nickel cobalt manganese) particles from directly contacting the electrolyte, and prevent the positive electrode material from oxidizing with the electrolyte to produce gas and heat under high voltage; W has good electrical conductivity and chemical stability as well as excellent thermal stability, which can not only improve the electronic transmission efficiency of the material, but also help to improve the thermal safety of the material; Zr and Sr affect the lattice parameters and crystal structure stability of the material, help to reduce the phase change and structural degradation of the material, thereby improving the cycle life and stability of the battery.
[0062] In an optional embodiment, the content A of Al element, the content B of Zr element, the content C of W element and the content D of Sr element in the positive electrode active material of the positive electrode active material layer satisfy the following relationship: 0.16≤A*C / (B*D)≤0.8; wherein 800ppm≤A≤1200ppm, 2500ppm≤B≤3500ppm, 700ppm≤C≤1000ppm, 600ppm≤D≤1000ppm. Studies have found that the ratio of A*C to B*D should not be too large, otherwise it will hinder the insertion and extraction of lithium ions, thereby reducing the electrochemical properties of the material. At the same time, it may also increase the resistance of the material and affect the transmission efficiency of electrons. But it cannot be too small, otherwise the thermal stability of the material cannot be guaranteed. When A*C / (B*D) is within the above range, the positive electrode active material has both excellent electrochemical properties and high thermal stability. As an example, A*C / (B*D) can be 0.16, 0.2, 0.4, 0.5, 0.6, 0.8, or within the range of any two of the above values. A can be 800ppm, 850ppm, 900ppm, 950ppm, 1000ppm, 1100ppm, 1200ppm, or within the range of any two of the above values. B can be 2500ppm, 2800ppm, 3000ppm, 3500ppm, or within the range of any two of the above values. C can be 700ppm, 750ppm, 800ppm, 850ppm, 900ppm, 1000ppm, or within the range of any two of the above values. D can be 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, or within the range of any two of the above values.
[0063] In an optional embodiment, the thickness H2 of the bottom coating layer in the positive electrode sheet, the thickness H1 of the positive electrode active material layer, the particle size Dv2(50) of the metal oxide of the bottom coating layer, and the particle size Dv1(50) of the positive electrode active material layer satisfy the following relationship: 2.67≤{H1*Dv1(50)} / {H2*Dv2(50)}≤833.33; wherein 2μm≤H2≤15μm; 40μm≤H1≤100μm, 1μm≤Dv1(50)≤5μm, 0.3μm≤Dv2(50)≤1μm; research has found that the ratio of H1*Dv1(50)} to {H2*Dv2(50) should not be too large, otherwise the resistance of the battery will increase, affecting the transmission efficiency of lithium ions. However, it should not be too small, otherwise the battery capacity and energy density will decrease, affecting the overall performance of the battery. When {H1*Dv1(50)} / {H2*Dv2(50)} is within the above range, the lithium-ion battery has high energy density, excellent cycle performance and excellent overcharge safety performance. The particle size Dv2(50) of the undercoat particles has an important influence on the conductivity and uniformity of the undercoat. When Dv2(50) is between 0.3μm and 1μm, a dense conductive network can be formed. At the same time, when the thickness H2 of the undercoat is between 2μm and 15μm, a uniform conductive network can be formed, and the energy density of the battery will not be affected by excessive thickness. Since the positive electrode structure adopts a double-layer coating design, namely the undercoat and the positive electrode active material layer, an interface is added. The undercoat is located between the positive electrode current collector and the positive electrode active material layer. When the particle size Dv1(50) of the positive electrode active material is between 1 μm and 5 μm, the small-particle undercoat layer can form a good match with the large-particle positive electrode active material layer, and the raised position of the undercoat layer and the recessed position of the positive electrode active material layer, as well as the recessed position of the undercoat layer and the raised position of the positive electrode active material layer can be in close contact, thereby reducing the contact impedance between the undercoat layer and the positive electrode active material layer and improving the conductivity of the battery. The positive electrode active material layer, as the main carrier of the positive electrode active material, can accommodate enough active materials when its thickness H1 is between 40 μm and 100 μm, thereby providing a high battery capacity. In addition, the internal resistance of the metal oxide particles in the undercoat layer will continue to increase during overcharging, so that the overcharge voltage quickly reaches the overcharge voltage cutoff point, thereby avoiding the battery from failing due to thermal runaway caused by overcharging. In summary, when {H1*Dv1(50)} / {H2*Dv2(50)} is between 2.67 and 833.33, the synergistic effect of these parameters enables the battery to have high energy density, excellent cycle performance and good overcharge safety performance. As an example, {H1*Dv1(50)} / {H2*Dv2(50)} can be 2.67, 5, 10, 100, 200, 500, 800, 833.33 or within the range of any two of the above values.H2 can be 2μm, 4μm, 6μm, 10μm, 15μm or within the range of any two of the above values. H1 can be 40μm, 50μm, 60μm, 80μm, 100μm or within the range of any two of the above values. Dv1(50) can be 1μm, 2μm, 3μm, 4μm, 5μm or within the range of any two of the above values. Dv2(50) can be 0.3μm, 0.4μm, 0.6μm, 0.8μm, 1μm or within the range of any two of the above values. When tin oxide and antimony oxide are coated on the surface of titanium dioxide, the particle size Dv2(50) of the metal oxide of the undercoating refers to the particle size Dv50 of the titanium dioxide after coating. When tin oxide, antimony oxide and titanium dioxide are mixed to form a mixture, the particle size Dv2(50) of the metal oxide of the undercoat layer is the overall particle size Dv50 of the mixture obtained after the tin oxide, antimony oxide and titanium dioxide are mixed. The particle size Dv2(50) of the metal oxide of the undercoat layer in the above two cases is measured by a laser particle size analyzer.
[0064] In an optional embodiment, the electrode sheet surface resistance of the positive electrode sheet is 600-2000mΩ. The electrode sheet surface resistance can be 600mΩ, 800, 1000mΩ, 1200mΩ or in the range of any two of the above values. The electrode sheet surface resistance within this range does not have an adverse effect on the electrical performance of the battery. As the overcharge voltage increases, the polarization phenomenon inside the battery gradually intensifies, and the battery voltage quickly reaches the overcharge cut-off voltage, thereby effectively preventing the battery from thermal runaway.
[0065] In an optional embodiment, the single-sided coating density of the positive electrode is 7 mg / cm 2 -14mg / cm 2 ; and / or, the compaction density of the positive electrode is 2.9g / cm 3 -3.5g / cm 3 and / or the porosity of the positive electrode sheet is 20%-40%. By controlling the single-sided coating surface density of the positive electrode sheet, the compaction density of the positive electrode sheet and / or the porosity of the positive electrode sheet within the above range, the battery can meet high charge and discharge rates and energy densities while having excellent cycle performance. As an example, the single-sided coating surface density of the positive electrode sheet is 7 mg / cm 2 , 8mg / cm 2 、10mg / cm 2 、10mg / cm 2 、14mg / cm 2 Or within the range of any two of the above values, the compaction density of the positive electrode is 2.9g / cm 3 、3.0g / cm 3 、3.2g / cm3 、3.4g / cm 3 , 3.5g / cm 3 Or within the range formed by any two of the above values, the porosity of the positive electrode sheet is 20%, 22%, 24%, 26%, 28%, 30% or within the range formed by any two of the above values.
[0066] In an optional embodiment, the primer layer also includes a first binder; preferably, the surface resistance R0mΩ of the primer layer, the surface resistance R1mΩ of the positive electrode sheet, and the content W of the first binder in the primer layer satisfy the following relationship: 30≤W*R0*R1≤3000; wherein R0 is 5-30, R1 is 600-2000, and W is 1%-5%. Studies have found that the product of W, R0 and R1 should not be too large, otherwise it will significantly reduce the conductivity of the positive electrode sheet, aggravate the polarization phenomenon, increase the heat generation during battery operation, and accelerate the deterioration of the internal material structure with the cycle, thereby causing a significant decrease in cycle performance. At the same time, the contact between the materials is too close and lacks sufficient thermal buffer space. Under extreme conditions such as overcharging, thermal runaway may be more likely to occur. But it cannot be too small, otherwise the primer layer will not be able to effectively adhere the positive active material to the current collector, causing the material to fall off or delaminate, affecting the structural stability and cycle life of the battery. When W*R0*R1 (denoted as R, that is, R=W*R0*R1) is within the above range, the lithium-ion battery has high energy density, excellent cycle performance and can pass 2C-6V overcharge safety performance. Preferably, 192≤W*R0*R1≤1250, and the overall performance of the battery is better in this range. As an example, the relationship W*R0*R1 can be 35, 50, 180, 200, 500, 800, 1250 or within the range of any two of the above values. R0 can be 5, 10, 20, 30 or within the range of any two of the above values. R1 can be 600, 800, 1000, 1200 or within the range of any two of the above values. W can be 1%, 3%, 5% or within the range of any two of the above values.
[0067] In a second aspect, the present application provides a lithium-ion secondary battery, comprising the positive electrode sheet described in the second aspect of the present application.
[0068] In an optional embodiment, the charging differential capacitance curve obtained by charging the lithium ion secondary battery at a rate of 2C in the voltage range of 2.5V-6V does not show a characteristic peak between 4.9V-5.5V, or the peak P1 between 4V-4.5V and the peak P2 between 4.9V-5.5V satisfy the following relationship: 0<peak intensity of peak P2 / peak intensity of P1≤0.3. The voltage range between 4.9V-5.5V is where the structure of the positive electrode material changes, so a characteristic peak will appear. The reduction or even disappearance of the characteristic peak indicates that the positive electrode sheet of the lithium ion battery with the above characteristics can ensure the stability of the positive electrode material structure within this voltage range, thereby effectively preventing thermal runaway caused by overcharging of the battery. It can also be seen from the overcharge curve that within this voltage range, the voltage rises rapidly to reach the overcharge cut-off voltage. Due to the increase in the internal resistance of the electrode sheet during the overcharging process, the temperature rise also increases to a certain extent, but after entering the constant voltage section, the temperature gradually decreases to room temperature.
[0069] In an optional embodiment, the lithium ion secondary battery further includes a negative electrode and an electrolyte. The negative electrode and the electrolyte may include any technology disclosed in the prior art.
[0070] In an optional embodiment, the preparation method of the metal oxide in the bottom coating in the present application can be a coprecipitation method, taking a soluble salt of tin or antimony and a precipitant to react in the presence of titanium dioxide and water to obtain a metal oxide. The soluble salts of tin and antimony include but are not limited to at least one of halogen salts, nitrates, and sulfates of tin and antimony, and the precipitant includes but is not limited to at least one of sodium hydroxide, potassium hydroxide, ammonium carbonate, sodium carbonate, and sodium bicarbonate. Wherein each raw material can be formulated according to the mass percentage of each oxide in the metal oxide, for example. The halogen salt in the present invention includes at least one of hydrochloride, bromate, iodate, or fluoride. A dispersant, such as polyethylene glycol (PEG), can also be added to the reaction system.
[0071] In an optional embodiment, the reaction temperature is 80-120° C. and the reaction time is 2-3 hours.
[0072] In an optional embodiment, the pH value of the aqueous solution of soluble salts of tin and antimony is adjusted to 8-9 by a precipitant, and then mixed with the titanium dioxide suspension for reaction. The solvent of the titanium dioxide suspension is water, and the concentration is 0.05-0.5 g / mL. After the reaction, filtering, grinding, washing and drying are performed.
[0073] In an optional embodiment, the preparation method of the metal oxide in the present application can be a ball milling method, in which tin oxide (SnO2), antimony oxide (Sb2O3), and titanium dioxide (TiO2) are mixed and ball milled to obtain the metal oxide.
[0074] In some embodiments of the present application, in order to reduce the agglomeration between particles, an appropriate amount of anhydrous ethanol or isopropanol can be added as a dispersant during the ball milling process.
[0075] In some embodiments of the present application, the ball milling time is set to 4-6 hours, and the rotation speed is controlled at 200-300 rpm.
[0076] In some embodiments of the present application, a drying step is further included after ball milling, with the temperature set at 80-100° C. and the drying time being 6-8 hours. The drying can be carried out in a vacuum drying oven or a forced air drying oven.
[0077] In some embodiments of the present application, the positive electrode active material in the positive electrode active material layer can be prepared by mixing a nickel source, a cobalt source, a manganese source and a lithium source to obtain a precursor, and then mixing it with a coating material, calcining it, and preparing it. The nickel source, cobalt source, manganese source and lithium source include but are not limited to at least one of oxides, hydroxide halides, nitrates and sulfates of nickel, cobalt, manganese and lithium.
[0078] In an optional embodiment, the calcination atmosphere is oxygen or inert gas, the heating rate is 1-8°C / min, and the temperature is raised to 700-900°C and then kept at this temperature for 8-12 hours.
[0079] In the present application, the single-sided coating surface density of the positive electrode sheet is measured by a ten-thousandth balance. The current collector and the double-sided positive electrode sheet after rolling are cut into discs with a diameter of 50 mm. Five pieces are randomly cut, and the average weight of the current collector is S1, and the average weight of the positive electrode sheet is S2. The single-sided coating surface density S = (S2-S1) / (2*area of the disc). Method for determining the compaction density of the positive electrode sheet: The thickness of the double-sided positive electrode sheet after rolling is measured as T, and the compaction density = S / (2*T). Method for determining the porosity of the positive electrode sheet: Based on Bohr's law of inert gas (such as helium) under certain conditions, the true volume of the sample is accurately measured by a true density meter to obtain its porosity. The porosity can be calculated by the following formula: Porosity = (apparent volume-true volume) / apparent volume×100%.
[0080] The present application is further described in detail below in conjunction with specific examples, which should not be construed as limiting the scope of protection claimed in the present application. In all examples and comparative examples of the present application, the unit wt% represents the mass percentage content.
[0081] Example A1
[0082] This embodiment provides a positive electrode sheet. Figure 1, comprising a current collector 100, a primer layer 101 located on both sides of the current collector and a positive electrode active material layer 102 located on the side of the primer layer away from the current collector, the primer layer comprising a metal oxide, based on the total mass of the metal oxide being 100%, the metal oxide comprising 58wt% of titanium dioxide, 38wt% of tin oxide and 4wt% of antimony oxide, the positive electrode active material layer comprising lithium nickel cobalt manganese oxide and a coating layer coated on the surface of the lithium nickel cobalt manganese oxide, the chemical formula of the lithium nickel cobalt manganese oxide is as follows: Li(Ni 0.9 Co 0.05 Mn 0.05 The coating layer comprises aluminum oxide Al2O3, zirconium dioxide ZrO2, tungsten oxide WO3 and strontium oxide SrO, and based on the weight of the positive electrode active material, the Al element content (denoted as A) is 1000ppm, the Zr element content (denoted as B) is 3000ppm, the W element content (denoted as C) is 900ppm, and the Sr element content (denoted as D) is 820ppm.
[0083] The preparation method is as follows:
[0084] (1) Preparation of metal oxide particles
[0085] ① Preparation of titanium dioxide suspension: Mix 10 g of titanium dioxide powder with deionized water, and stir continuously at 60° C. to prepare a titanium dioxide suspension with a concentration of 0.1 g / mL.
[0086] ② Adding a dispersant: Add 1.0% of the mass of titanium dioxide as a dispersant polyethylene glycol (PEG) to the titanium dioxide suspension, and stir and perform ultrasonic treatment.
[0087] ③ Adjust the pH value: add alkaline solution (sodium hydroxide solution, weight concentration 8%) to adjust the pH value of the mixed solution to 8.5.
[0088] ④ Coating treatment: put the mixed solution into a reactor, heat it to 85°C (this temperature is recorded as the synthesis temperature), add 408.6mL of 0.02g / mL stannous chloride aqueous solution and 50.8ml of 0.02g / mL antimony trichloride aqueous solution into the reactor, react at 85°C for 3 hours.
[0089] ⑤ Filtration and grinding: Filter through the sedimentation tank, put the filtered material into the grinder and grind it thoroughly for 60 minutes.
[0090] ⑥ Cleaning and drying: The ground material is cleaned with ethanol and then dried to obtain the desired metal oxide particles. The tin oxide and antimony oxide in the obtained metal oxide particles are coated on the surface of titanium dioxide to form a coating layer. The microstructure of the sample is observed by using a transmission electron microscope (TEM) to penetrate the sample using a high-energy electron beam and an image formed by the interaction between electrons and atoms in the sample. Under TEM, the titanium dioxide particles and the tin oxide and antimony oxide coating layers thereon can be clearly seen. The coating thickness measured by TEM is shown in Table 1. The particle size Dv2 (50) of the obtained metal oxide particles is tested by a laser particle size analyzer, as shown in Table 1.
[0091] (2) Preparation of positive electrode active materials
[0092] ① Select a high-purity nickel source (NiO), a high-purity cobalt source (CoO) and a manganese source (MnO2), weigh them according to the molar ratio of Ni:Co:Mn=90:5:5, and select an appropriate lithium source (lithium hydroxide is selected in this embodiment);
[0093] ② Mix the nickel source, cobalt source, manganese source and lithium source in a molar ratio of Li: (Ni+Co+Mn) = 1:1 to form a lithium nickel cobalt oxide precursor;
[0094] ③ According to the mass content of each metal element in the entire positive electrode active material, high-purity aluminum oxide, zirconium oxide, tungsten oxide, and strontium oxide powders are weighed and uniformly mixed with the lithium nickel cobalt oxide precursor;
[0095] ④ The coated precursor obtained in step ③ was heated to 850°C (this temperature is recorded as the calcination temperature) at a rate of 5°C / min in an oxygen atmosphere for calcination for 10 hours, and then cooled to room temperature.
[0096] ⑤ The calcined product was ground (speed 850r / min, time 120min) to obtain a positive electrode active material with the required particle size distribution and the surface coated with aluminum oxide, zirconium oxide, tungsten oxide and strontium oxide. The chemical formula of the positive electrode active material, the mass content of each metal element, the particle size Dv1(50) of the positive electrode active material and the calculation results of A*C / (B*D) are shown in Table 1.
[0097] (3) Preparation of primer layer
[0098] The metal oxide particles and the first binder (polyvinylidene fluoride) were mixed in a mass ratio of 97:3, added to an N-methylpyrrolidone (NMP) solution, and stirred evenly to form a slurry with a solid content of 40%. Then, the slurry was evenly coated on the positive electrode current collector and baked (temperature 80°C, time 10h) to obtain a primer layer. The thickness H2 of the primer layer is shown in Table 2.
[0099] (4) Preparation of positive electrode active material layer
[0100] The positive electrode active material, conductive agent (composition of carbon nanotubes and conductive carbon black with a mass ratio of 1:2) and binder (PVDF) were weighed according to a mass ratio of 96:1.4:1.6, and N-methylpyrrolidone (NMP) was added after the positive electrode active material, conductive agent and binder were mixed and uniformly mixed to form a positive electrode slurry with a solid content of 65%. The positive electrode slurry was uniformly coated on the positive electrode current collector aluminum foil, and baked (temperature 80°C, time 10h) to obtain a positive electrode active material layer. The thickness H1 of the positive electrode active material layer and the result values of {H1*Dv1(50)} / {H2*Dv2(50)} are shown in Table 2. After roller pressing and slitting, the positive electrode sheet to be wound was obtained. The single-sided coating surface density, compaction density and porosity of the positive electrode sheet were measured respectively, as shown in Table 2.
[0101] This embodiment also provides a lithium ion secondary battery prepared by the following method:
[0102] Graphite, conductive carbon black, binder carboxymethylcellulose (CMC) and styrene utadiene rubber (SBR) are mixed in a mass ratio of 96:1.5:1.5:1, and then a certain amount of deionized water is added to mix and stir in a mixer, and the mixture is evenly dispersed to obtain a negative electrode slurry with a solid content of 45% to be coated; the slurry is coated on a 6μm copper foil current collector, and after drying, it is rolled, cut and sliced to obtain a negative electrode sheet to be wound. The positive and negative electrode sheets to be wound are taken and used through winding, packaging and baking, liquid injection (lithium hexafluorophosphate (LiPF6), solvent (DEC and EC volume ratio is 5:5), additive FEC according to the mass ratio of 17%:80%:3%), hot pressing at 80 degrees, and conventional formation to prepare a finished battery.
[0103] The preparation method of the positive electrode sheets in Examples A2-A5 is basically the same as that in Example A1. The volumes of the stannous chloride aqueous solution and the antimony trichloride aqueous solution used in the preparation of the metal oxide particles are different, resulting in different contents of each oxide in the metal oxide, see Table 1 for details.
[0104] The preparation method of the positive electrode sheet in Examples A6-A7 is basically the same as that in Example A1, except that the molar ratio of nickel, cobalt and manganese elements during the preparation of lithium nickel cobalt manganese oxide results in a different molecular formula of lithium nickel cobalt manganese oxide, as shown in Table 1 for details.
[0105] The preparation method of the positive electrode sheet in Examples A8-A9 is basically the same as that in Example A1, except that the content of each coating element in the coating layer is different, see Table 1 for details.
[0106] The preparation method of the positive electrode sheet in Example A10 is basically the same as that in Example A1, except that the synthesis temperature of the metal oxide particles is adjusted to 80° C. to obtain metal oxide particles with different particle sizes Dv2 (50), as shown in Table 1 for details.
[0107] The preparation method of the positive electrode sheet in Example A11 is basically the same as that in Example A1, except that the synthesis temperature of the metal oxide particles is adjusted to 110° C. to obtain metal oxide particles with different particle sizes Dv2 (50), as shown in Table 1 for details.
[0108] The preparation method of the positive electrode sheet in Example A12 is basically the same as that in Example A1, except that the synthesis temperature of the metal oxide particles is adjusted to 120° C. to obtain metal oxide particles with different particle sizes Dv2 (50), as shown in Table 1 for details.
[0109] The preparation method of the positive electrode sheet in Example A13 is basically the same as that in Example A1, except that the calcination temperature of the positive electrode active material is adjusted to 700° C. to obtain positive electrode active materials with different particle sizes, as shown in Table 2 for details.
[0110] The preparation method of the positive electrode sheet in Example A14 is basically the same as that in Example A1, except that the calcination temperature of the positive electrode active material is adjusted to 750° C. to obtain positive electrode active materials with different particle sizes, as shown in Table 2 for details.
[0111] The preparation method of the positive electrode sheet in Example A15 is basically the same as that in Example A1, except that the calcination temperature of the positive electrode active material is adjusted to 900° C. to obtain positive electrode active materials with different particle sizes, as shown in Table 2 for details.
[0112] The preparation method of the positive electrode sheet in Examples A16-A21 is basically the same as that in Example A1, except that the thickness of the undercoat layer and / or the positive electrode active material layer is different, see Table 2 for details.
[0113] The preparation method of the positive electrode sheet in Examples A22-A23 is basically the same as that in Example A1, except that the content of the first binder polyvinylidene fluoride in the primer layer is different, see Table 2 for details.
[0114] The preparation method of the positive electrode sheet in Example A24 is basically the same as that in Example A1, except that the positive electrode active material and the preparation method are different. The positive electrode active material in Example A24 includes nickel-doped lithium manganese oxide and a coating layer coated on the surface of the nickel-doped lithium manganese oxide. The chemical formula of the nickel-doped lithium manganese oxide is as follows: LiMn 1.9 Ni 0.1The coating layer comprises aluminum oxide Al2O3, zirconium dioxide ZrO2, tungsten oxide WO3 and strontium oxide SrO, and based on the weight of the positive electrode active material, the Al element content (denoted as A) is 1000ppm, the Zr element content (denoted as B) is 3000ppm, the W element content (denoted as C) is 900ppm, and the Sr element content (denoted as D) is 820ppm.
[0115] The preparation method is as follows: according to the molar ratio of Mn:Ni=19:1 and the molar ratio of Li:(Mn+Ni)=1:2, high-purity manganese dioxide, nickel oxide and lithium source (lithium hydroxide) are weighed, and high-purity aluminum oxide, zirconium oxide, tungsten oxide and strontium oxide powders are weighed according to the mass content of each metal element in the entire positive electrode active material. After mixing the raw materials, calcination is carried out in an inert atmosphere (argon) at a calcination temperature of 850°C for 4 hours, and the calcined product is ground to obtain the first positive electrode material with the required particle size distribution.
[0116] The preparation methods of the lithium-ion secondary batteries in Examples A2 to A24 are similar to those in Example A1, except that the positive electrode sheets are prepared using the positive electrode sheets prepared in Examples A2 to A24 of the present application, respectively.
[0117] The preparation method of the positive electrode sheet in Comparative Example A1 is substantially the same as that in Example A1, except that the preparation of the undercoat layer is omitted, and the prepared electrode sheet only includes the positive electrode active material layer, see Figure 2 .
[0118] The preparation methods of the lithium ion secondary battery in Comparative Example A1 are similar to those in Example A1, except that the positive electrode sheets are prepared using the positive electrode sheets prepared in Comparative Example 1 of the present application.
[0119] Table 1 Structure and performance parameters of positive electrode
[0120]
[0121]
[0122] Table 2 Structure and performance parameters of positive electrode
[0123]
[0124] “ / ” means it does not exist.
[0125] Example B1
[0126] This embodiment provides a positive electrode sheet, which is basically the same as Embodiment A1, except that the preparation method of the metal oxide particles is different. In the metal oxide particles of this embodiment, tin oxide, antimony oxide and titanium dioxide are directly mixed to form a mixture.
[0127] The preparation method of the metal oxide particles of this embodiment is as follows:
[0128] Use a mixed powder of high-purity tin oxide (SnO2) and antimony oxide (Sb2O3) and titanium dioxide (TiO2) powder. According to the composition ratio of the target metal oxide particles, SnO2:Sb2O3:TiO2=58:38:4, weigh the corresponding mass of raw materials and mix them using a high-energy ball mill or a planetary ball mill. Put the weighed tin oxide, antimony oxide and titanium dioxide powders into a ball mill, and add 1.5 times the amount of anhydrous ethanol as the mixed powder. The ball milling time is set to 5 hours, and the speed is controlled at 300 rpm. Pour the mixed slurry into a drying tray. The temperature is set to 85°C and the drying time is 6 hours until the slurry is completely dried into a powder. Use a sieve with a mesh size of 800 to sieve the dried powder. Use a laser particle size analyzer to test the particle size of the metal oxide particles, and the particle size Dv2(50) of the entire metal oxide particles is measured as shown in Table 3. The primary particle size Dv(50) and secondary particle size Dv(50) of tin oxide and antimony oxide and the particle size Dv(50) of titanium dioxide used in the preparation process are shown in Table 3. The primary particle size was measured by SEM, and the secondary particle size was measured by a laser particle size analyzer.
[0129] The preparation method of the positive electrode sheet in Example B2 is basically the same as that in Example B1, except that the particle size of the titanium dioxide powder is different, resulting in different particle size parameters of the metal oxide particles, as shown in Table 3 for details.
[0130] The preparation method of the positive electrode sheet in Example B3 is basically the same as that in Example B1, except that the particle size of the titanium dioxide powder is different, resulting in different particle size parameters of the metal oxide particles, as shown in Table 3 for details.
[0131] The preparation method of the positive electrode sheet in Example B4 is basically the same as that in Example B1, except that the particle size of the titanium dioxide powder is different, resulting in different particle size parameters of the metal oxide particles, as shown in Table 3 for details.
[0132] The preparation method of the positive electrode sheet in Example B5 is basically the same as that in Example B1, except that the calcination temperature of the positive electrode active material is adjusted to 700° C. to obtain positive electrode active materials with different particle sizes, as shown in Table 4 for details.
[0133] The preparation method of the positive electrode sheet in Example B6 is basically the same as that in Example B1, except that the calcination temperature of the positive electrode active material is adjusted to 750° C. to obtain positive electrode active materials with different particle sizes, as shown in Table 4 for details.
[0134] The preparation method of the positive electrode sheet in Example B7 is basically the same as that in Example B1, except that the calcination temperature of the positive electrode active material is adjusted to 900° C. to obtain positive electrode active materials with different particle sizes, as shown in Table 4 for details.
[0135] The preparation method of the positive electrode sheets in Examples B8-B13 is basically the same as that in Example B1, except that the thickness of the undercoat layer and / or the positive electrode active material layer is different, see Table 4 for details.
[0136] Table 3 Structure and performance parameters of positive electrode
[0137]
[0138]
[0139] Table 4 Structure and performance parameters of positive electrode
[0140]
[0141] Test Case
[0142] 1. SEM and XRD testing
[0143] Figure 3 The surface SEM images of the pole pieces prepared in Example A1 and Comparative Example A1; Figure 4 The cross-sectional SEM images of the pole pieces prepared in Example A1 and Comparative Example A1 are shown in FIG. Figure 7 This is a SEM image of the electrode piece coated with the primer layer in step (3) of Example A1.
[0144] XRD curves of the electrode sheet coated with the primer layer obtained in step (3) of Example A1 and the positive electrode sheet prepared in Comparative Example A1; see Figure 6 As shown in the figure, it can be seen that in the XRD spectrum of the material of the base coating, there are characteristic peaks at 25.325°, 26.832°, 34.196°, 36.989°, 37.841°, 38.601°, 48.074°, 52.230°, 53.952°, 55.106°, 62.750°, 68.842°, 70.346° and 75.129°. Among them, 26.832°, 34.196° and 52.230° are the characteristic peaks of SnO2, and 25.325°, 36.989°, 37.841°, 38.601°, 48.074°, 53.952°, 55.106°, 62.750°, 68.842°, 70.346° and 75.129° are the characteristic peaks of TiO2.
[0145] 2. Discharge differential capacitance curve test
[0146] The lithium-ion secondary batteries prepared in the embodiments and comparative examples were charged at a 2C rate, and the voltage V and battery capacity Q of the first charge were measured. The discharge differential capacitance curve was obtained with the voltage as the horizontal axis and the dQ / dV value obtained by differentiating the battery capacity Q with the voltage V as the vertical axis. The charging voltage range was 2.5V-6V. Among them, peak P1 is the peak with the highest dQ / dV value in the voltage range of 4V-5.5V in the charge differential capacitance curve; peak P2 is the characteristic peak of the positive electrode material between 4.9V-5.5V (structural change collapse), and the ratio of the dQ / dV value (peak intensity) of peak P2 to peak P1 is shown in Tables 2 and 4. Figure 5 It can be seen from Tables 2 and 4 that, compared with Comparative Example A1, the discharge differential capacitance curves of the secondary batteries of the embodiments of the present invention have no characteristic peak between 4.9V and 5.5V, or the intensity of the characteristic peak is significantly reduced. The reduction or even disappearance of the characteristic peak indicates that the lithium-ion battery positive electrode sheet with the above characteristics can ensure the stability of the positive electrode material structure within this voltage range.
[0147] 3. Battery capacity, thickness and energy density test
[0148] The prepared finished battery was charged to full power at constant current and constant voltage at 25°C, and then discharged to 3.0V at 0.5C, and the discharged capacity was recorded as the battery capacity;
[0149] The finished battery was charged to 30% SOC at 25°C, and the battery thickness was tested using 600g PPG.
[0150] Calculate volume energy density = battery capacity * platform voltage / battery length / width / thickness.
[0151] 4. Cycle test
[0152] The prepared finished battery was charged and discharged at 3C / 10C at 25°C, and the battery capacity retention rate and expansion rate were confirmed after 600 cycles. 600-week capacity retention rate = remaining capacity / initial capacity*100%, thickness expansion rate = (final thickness-initial thickness) / initial thickness*100%.
[0153] 5. Overcharge test
[0154] The lithium-ion batteries of the above embodiments and comparative examples were subjected to 2C-5V overcharge, 2C-6V and 2C-7V overcharge tests. The test method was as follows: at 25°C, the feed battery was charged to 5V, 6V or 7V at a constant current and constant voltage of 2C, and maintained at 5V, 6V or 7V for 7 hours. The battery passed the test if it did not catch fire or explode. Twenty batteries were tested in each group, and the number of batteries that passed the test was recorded.
[0155] Please see Table 5-Table 6 for the above test results.
[0156] Table 5 Electrical properties of lithium-ion secondary batteries
[0157]
[0158]
[0159] Table 6 Cycle performance and safety of lithium-ion secondary batteries
[0160]
[0161]
[0162] It can be seen from Table 5 that the capacity, thickness and volume energy density of each embodiment are equivalent to those of the comparative example, but the internal resistance of the embodiment is slightly higher than that of the comparative example, indicating that the presence of the bottom coating layer will slightly increase the internal resistance of the battery.
[0163] As can be seen from Table 6, the capacity retention rate and expansion rate of the embodiment and the comparative example after 600 cycles at 25 degrees are similar, indicating that the presence of the primer layer does not affect the cycle performance of the battery.
[0164] From Table 6 and Fig. 9 It can be seen that the examples can pass the test under 2C-5V overcharge and 2C-6V overcharge conditions, and most of the 2C-7V overcharge tests can pass the test, while the comparative examples all fail, indicating that the presence of the primer layer can significantly improve the overcharge performance of the battery. From the overcharge curve ( Figure 8 ) It can also be seen that the presence of the undercoat layer enables the battery to quickly reach the overcharge cut-off voltage, thereby ensuring that the positive electrode material will not be damaged and avoiding thermal runaway. Fig.10 It can be seen that after overcharging, the bottom coating layer is separated from the current collector, thereby achieving overcharge protection. In summary, the present invention can significantly improve the overcharge performance of the lithium-ion battery while maintaining good cycle performance through the provision of the bottom coating layer.
[0165] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection created by this application.
Claims
1. A positive electrode sheet, characterized in that: The positive electrode sheet includes a current collector, a primer layer located on at least one side of the current collector, and a positive electrode active material layer located on the side of the primer layer away from the current collector, the primer layer includes a metal oxide, and based on the total mass of the metal oxide as 100%, the metal oxide includes 50%-70% of titanium dioxide, 25%-40% of tin oxide, and greater than 0 and less than or equal to 25% of antimony oxide, and the tin oxide and antimony oxide are coated on the surface of titanium dioxide to form a coating layer and / or are mixed with titanium dioxide to form a mixture.
2. The positive electrode sheet according to claim 1, characterized in that: Taking the total mass of the metal oxide as 100%, the mass content of titanium dioxide is 55%-65%, the mass content of tin oxide is 26%-36%, and the mass content of antimony oxide is 4%-9%.
3. The positive electrode sheet according to claim 1 or 2, characterized in that: When the tin oxide and antimony oxide are coated on the surface of titanium dioxide to form a coating layer, the thickness of the coating layer is 20-100 nm; the particle size Dv2(50) of the coated titanium dioxide is 0.3-1 μm; and / or, When the tin oxide, antimony oxide and titanium dioxide are mixed to form a mixture, the primary particle size Dv(50) of the tin oxide and antimony oxide is 5nm-20nm, the secondary particle size Dv(50) of the tin oxide and antimony oxide is 30nm-80nm; the particle size Dv(50) of titanium dioxide is 250nm-550nm.
4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The surface resistance of the primer layer is 5-30 mΩ; and / or the XRD spectrum of the primer layer has characteristic peaks at 25.125-25.525°, 26.632-27.032°, 33.996-34.396°, 36.789-37.189°, 37.641-38.041°, 38.401-38.801°, 47.874-48.274°, 52.030-52.430°, 53.752-54.152°, 54.906-55.306°, 62.550-62.950°, 68.642-69.042°, 70.146-70.546° and 74.929-75.329°.
5. The positive electrode sheet according to any one of claims 1 to 4, characterized in that: The positive electrode active material of the positive electrode active material layer includes lithium nickel cobalt manganese oxide, and the chemical formula of the lithium nickel cobalt manganese oxide is as follows: Li(Ni x Co y Mn z )O2, wherein x+y+z=1, 0.8≤x<1, 0<y<0.2, 0<z<0.2; preferably, the surface of the lithium nickel cobalt manganese oxide is provided with a coating layer, and the coating layer contains elements Al, Zr, W and Sr.
6. The positive electrode sheet according to claim 5, characterized in that: The content A of the Al element, the content B of the Zr element, the content C of the W element and the content D of the Sr element in the positive electrode active material of the positive electrode active material layer satisfy the following relationship: 0.16≤A*C / (B*D)≤0.8; Among them, 800ppm≤A≤1200ppm, 2500ppm≤B≤3500ppm, 700ppm≤C≤1000ppm, 600ppm≤D≤1000ppm.
7. The positive electrode sheet according to any one of claims 1 to 6, characterized in that: The thickness H2 of the undercoat layer, the thickness H1 of the positive electrode active material layer, the particle size Dv2(50) of the metal oxide of the undercoat layer, and the particle size Dv1(50) of the positive electrode active material of the positive electrode active material layer in the positive electrode sheet satisfy the following relationship: 2.67≤{H1*Dv1(50)} / {H2*Dv2(50)}≤833.33; Among them, 2μm≤H2≤15μm; 40μm≤H1≤100μm, 1μm≤Dv1(50)≤5μm, 0.3μm≤Dv2(50)≤1μm; preferably, 50μm≤H1≤80μm, 3μm≤H2≤6μm, 2μm≤Dv1(50)≤4μm, 0.35μm≤Dv2(50)≤0.8μm, 33.3≤{H1*Dv1(50)} / {H2*Dv2(50)}≤304.
76.
8. The positive electrode sheet according to any one of claims 1 to 7, characterized in that: The single-sided coating density of the positive electrode is 7 mg / cm 2 -14mg / cm 2 ; and / or, the compaction density of the positive electrode is 2.9g / cm 3 -3.5g / cm 3 and / or, the porosity of the positive electrode sheet is 20%-40%; and / or, the surface resistance of the positive electrode sheet is 600-2000mΩ.
9. The positive electrode sheet according to any one of claims 1 to 8, characterized in that: The primer layer further includes a first binder; preferably, the surface resistance R0mΩ of the primer layer, the surface resistance R1mΩ of the positive electrode sheet, and the content W of the first binder in the primer layer satisfy the following relationship: 30≤W*R0*R1≤3000, preferably, 192≤W*R0*R1≤1250; Among them, R0 is 5-30, R1 is 600-2000, and W is 1%-5%.
10. A lithium ion secondary battery, characterized in that: A positive electrode sheet comprising any one of claims 1 to 9; optionally, the charging differential capacitance curve of the lithium ion secondary battery charged at a rate of 2C in a voltage range of 2.5V-6V does not show a characteristic peak between 4.9V-5.5V, or the peak intensity P1 of the characteristic peak 1 between 4V-4.5V and the peak intensity P2 of the characteristic peak 2 between 4.9V-5.5V satisfy the following relationship: <P2 / P1≤0.3。
Citation Information
Cited By
Positive plate, preparation method thereof and battery
CN120674433A
